Dissent and discipline in Ben Gurion's Labor Party, 1930-32 - Joel Perlmann (Levy Economics Institute of Bard College, 2006)
This paper describes a small opposition group that functioned during 193033 on the left fringes of Ben Gurion's Mapai party in Palestine. Mapai dominated Jewish Palestine's politics, and later the politics of the young State of Israel; it lives on today in Israel's Labor Party. The opposition group, probably no more than a dozen active individuals at the outset, was comprised mostly of young adults, recently arrived from the Soviet Union or Poland. They put out a series of pamphlets, Reshimot Sozialistiyot (Socialist Notes), apparently held some public meetings and sought some minor party offices as well. These activities, and especially the pamphlets troubled Ben Gurion and the other party leaders. The leadership discussed the opposition group on 10 separate occasions at their private official meetings during 1932. They invited the opposition for an extensive clarification of views, and then insisted that the members cease functioning as an organized group. When that insistence failed to stop the publications, the leadership published a decree (written by party ideologue, B. Katznelson) expelling each of them from Mapai by name. The opposition's critique of Mapai revolved around the balance of internationalism inherent in socialism and nationalism inherent in Zionism. The party reaction showed 1) specific features of ideology that were unacceptable even to this eclectic party; 2) the leadership's concern for control and for disciplined followers; and 3) the nature of leadership discussion and behavior in regard to expulsion.
Keywords: 330